2001
DOI: 10.1385/bter:82:1-3:201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Oil- and Corn Oil-Enriched Diets on the Tissue Mineral Content in Mice

Abstract: The mineral content (zinc, iron, magnesium, and calcium) in the liver, spleen, and thymus of male Balb/C mice was analyzed. Animals were fed, over 21 d, diets enriched with corn oil (FCO diet) or olive oil (FOO diet) (5% addition to standard pellet, w/w). Olive oil with predominant oleic acid (C18:1, n-9) had a quite different composition than corn oil, in which linoleic acid (C18:2, n-6) prevails. The zinc and magnesium tissue concentrations were not changed in either group. The calcium concentration in liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Claassen et al, (1995) concluded that increased consumption of n-3 fatty acids increased Ca balance (mg / 24 h) by 41.5% in rats. In other research with mice, a 5% addition (w/w) of either corn oil (predominantly linoleic acid; n: 6) or olive oil (predominantly oleic acid; n:9) resulted in increased liver and spleen Ca concentrations (Milin et al, 2001) compared with the control diets (normal fat content), However in a study with young growing rats, the type of dietary fat (safflower oil, flaxseed oil, olive oil, or beef tallow), varying in concentrations of n-3, n-6, and n-9 fatty acids, had no effect on plasma and liver Ca and Fe concentrations in the presence of adequate dietary Ca (Shotton and Droke, 2004). Another evidence suggests that the type of dietary fat has an inhibitory effect on Ca metabolism when Ca intake is low (<0.4% of the diet by weight).…”
Section: Discussionmentioning
confidence: 87%
“…Claassen et al, (1995) concluded that increased consumption of n-3 fatty acids increased Ca balance (mg / 24 h) by 41.5% in rats. In other research with mice, a 5% addition (w/w) of either corn oil (predominantly linoleic acid; n: 6) or olive oil (predominantly oleic acid; n:9) resulted in increased liver and spleen Ca concentrations (Milin et al, 2001) compared with the control diets (normal fat content), However in a study with young growing rats, the type of dietary fat (safflower oil, flaxseed oil, olive oil, or beef tallow), varying in concentrations of n-3, n-6, and n-9 fatty acids, had no effect on plasma and liver Ca and Fe concentrations in the presence of adequate dietary Ca (Shotton and Droke, 2004). Another evidence suggests that the type of dietary fat has an inhibitory effect on Ca metabolism when Ca intake is low (<0.4% of the diet by weight).…”
Section: Discussionmentioning
confidence: 87%
“…A person needs a high level of essential fatty acids (PUFA) as a diet. The total percentage of PUFA constituted by linoleic acid (18:2) alone is about 60 percent in corn oil, while, the monounsaturated fatty acid (MUFA) (high canola, peanut, and olive oil concentrations), about 24 percent is MUFA (oleic acid; 18:1), Palmitic acid (16:0) is almost 13 percent among saturated fatty acids, and stearic acid (18:0) is 1 percent (Milin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Linoleic acid is necessary for the integrity of the cell membranes, skin, the immune system, and for synthesis of eicosanoids. Eicosanoids are necessary for cardiovascular, renal, reproductive and gastrointestinal functions (Milin et al, 2001). Many fatty acids are found in corn oil as palmitic acid, oleic acid, stearic acid, linoleic acid and linolenic acid (Si et al, 2014).…”
Section: Introductionmentioning
confidence: 99%